Analisis Kepribadian Tokoh Utama Novel Rumah Karya J.S. Khairen dalam Tinjauan Psikologi Sastra - Salma Nur Salsabila; Yermia Nugroho Agung Wibowo (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the personality of the main character and various factors that influence it in the novel Rumah by J.S. Khairen. This study uses a literary psychology approach with Gerardus Heymans' personality theory. Using qualitative descriptive methods, and data collection techniques that include reading techniques and note-taking techniques. This study uses data sources from the novel Rumah by J.S. Khairen, published in January 2026 with the first printing. Data analysis was carried out through intensive reading, data collection, data grouping, data analysis, and drawing conclusions. The results of the study produced the personality of the main character consisting of fourteen personality traits; empathy, patience, never giving up, responsibility, emotionality, expressiveness, calm, vengeful, caring, compassionate, independent, assertive, confident, and arrogant. The most dominant personality forms are emotionality with 19 data and caring with 14 data. Various factors that influence the personality of the main character include psychological experience factors in the family and psychological experience factors in work. The most dominant factor is the psychological experience factor in the family consisting of 54 data, while the psychological experience factor in work consists of 8 data. Based on the research results, it was concluded that the personality of the main character in the novel Rumah is complex, dynamic, and more influenced by psychological experiences within the family environment. Gerardus Heymans' theory is relevant for revealing the form of character personality in literary works.